Relatos dibujados: investigación biográfico-narrativa. Una propuesta documental desde la creación literaria - Arango Rodríguez, Selen Catalina (Folios, revista de la Facultad de Comunicaciones y Filología, 2019)
This essay analyzes the writing of the final text of a biographical-narrative research as an act of empathy that requires the matching of the biographies of researchers and the reports developed or compiled during the research process. Such process is explained through questions and reflections formulated during the reading of Birmajer’s short story Cicatrices [Scars]. This matching is described in the text as the act of drawing on the face, on one’s own formation. We review contributions by Gadamer, Grondin, Arfouch and Delory-Momberger.